The Iberian exception: An overview of its effects over its first 100 days - David Robinson; Ángel Arcos-Vargas; Michael Tennican; Fernando Nú\~nez (The Oxford Institute for Energy Studies, 2023)
This paper by David Robinson, Angel Arcos, Michael Tennican and Fernando Núnez offers an independent assessment of certain key economic effects of the Iberian Exception (IE), the common name for legal measures affecting the Iberian power market that were introduced in June 2022 by the Spanish and Portuguese governments. The governments' stated aim was to reduce the major component of electricity prices for many Iberian consumers, a component which was indexed to Iberian wholesale power market spot prices that were rising alarmingly due to extremely tight international markets for natural gas. According to the Iberian governments, this objective was to be attained by terms of the IE that subsidize a reduction in wholesale power market prices, with the subsidy financed in part by a new element added to the bills of consumers benefiting from that wholesale price reduction. Another Spanish governmental aim was to reduce the Government's published measure of inflation, which was linked to a regulated retail price indexed to Iberian wholesale spot power market prices. The Spanish Government maintains that, during its first 100 days, the IE provided substantial benefits for consumers affected by the IE, which included over 10 million small consumers as well as many large ones. However, the authors of this study question that view. We argue that the effect of the IE on retail prices depends critically on the assumptions about what would have occurred in the absence of the IE, that is, in a counterfactual scenario. The Government's counterfactual methodology ignores demand elasticity in Iberia and in France, and this inflates their estimate of immediate consumer benefits. Using hourly data on the wholesale electricity market for the first 100 days of the IE, this paper's analysis of alternative counterfactuals that reflect the effects of demand elasticity shows substantially lower benefits of the IE for consumers than the Spanish Government methodology suggests. The analysis here suggests that affected consumers could have paid somewhat less for the energy component of their electricity bills in the first 100 days of the IE, had it not been introduced. We also identify several other potential short- and long-term effects of the IE that deserve further study. These include increased margins for fossil-fired generators, reduced margins for some decarbonized inframarginal plant, heightened investor perceptions of regulatory risk, weakened incentives for efficient consumption, and higher carbon emissions and gas prices.
Keywords: 330; electricity market design; electricity market intervention; electricity price caps; European energy crisis; Excepción Ibérica; gas price caps; Iberian Exception; MIBEL; MIBGAS